A kind of anti-ultraviolet hygroscopic fiber and preparation method thereof

By coating Au@Cu2O/ZnO composite material on PET fiber and performing modification treatment, the problems of poor hygroscopicity and insufficient UV resistance in outdoor clothing fabrics are solved, and the fiber's hygroscopicity, antibacteriality and UV resistance are significantly improved.

CN118979315BActive Publication Date: 2025-02-28GUANGDONG MINGE APPARELS IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411266759.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-02-28
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

When used in outdoor clothing fabrics, PET fiber has poor hygroscopicity and insufficient UV resistance, making it difficult to meet the needs of outdoor sports.

Method used

By coating Cu2O on the surface of the gold nanorod and growing ZnO thereon, Au@Cu2O/ZnO composite material is formed as an additive, and reacted with ethylene glycol, isosorbide and terephthalic acid to form modified PET. Then the modified PET fiber is subjected to alkali leaching and deep treatment, and the hydrophilic modifier and epigallocate catechin gallate are grafted to improve the hygroscopic, antibacterial and anti-ultraviolet properties of the fiber.

Benefits of technology

The fiber has significantly improved the moisture absorption, antibacterial properties and UV resistance, making it more suitable for outdoor clothing fabrics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of textile fibers, and discloses an anti-ultraviolet moisture absorption fiber and a preparation method thereof. The preparation method of the anti-ultraviolet moisture absorption fiber comprises the following steps: after coating Cu2O on a gold nanorod, growing ZnO on its surface to obtain an Au@Cu2O / ZnO composite material; reacting the Au@Cu2O / ZnO composite material with ethylene glycol, isosorbide, and terephthalic acid to obtain a modified PET; mixing the modified PET with an anti-ultraviolet additive, melt spinning to obtain a modified PET fiber, and then treating to obtain an activated PET fiber; reacting 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt with a silane coupling agent KH560 to obtain a hydrophilic modifier; grafting the hydrophilic modifier and epigallocatechin gallate on the activated PET fiber to obtain an anti-ultraviolet moisture absorption fiber. The anti-ultraviolet moisture absorption fiber of the invention has good anti-ultraviolet performance, hygroscopic performance, and antibacterial performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of textile fibers, in particular to an anti-ultraviolet hygroscopic fiber and a preparation method thereof. Background Art

[0002] Polyester is the commercial name for polyethylene terephthalate (PET) fiber. It is one of the three main synthetic fibers along with polyamide fiber and polyacrylonitrile fiber, and is also the most widely used fiber in clothing fabrics. With the improvement of quality of life and the increase of work pressure, outdoor sports are becoming more and more popular. However, long-term outdoor sports are prone to sweating. The moisture absorption and perspiration wicking properties of fabrics can help to quickly drain away sweat and keep the skin dry and comfortable. However, polyester is a hydrophobic fiber. In addition to two terminal hydroxyl groups, the tightly arranged molecular structure has no other hydrophilic or polar groups, and has poor hygroscopicity. In order to solve the problem of poor hygroscopicity of PET fiber, Chinese patent CN117845364B discloses a preparation process of hygroscopic antibacterial fiber fabrics, wherein a benzisothiazolinone copolymer containing carboxyl and ether bonds is melt-spun with ethylene terephthalate to obtain PET polyester hygroscopic antibacterial fiber. The benzisothiazolinone copolymer contains hydrophilic carboxyl, ether and amide bonds. The PET polyester fiber obtained by blending and spinning has excellent hydrophilicity, which improves the hygroscopicity and wearing comfort of the fiber and its fabric. However, when the PET polyester hygroscopic antibacterial fiber is used in outdoor clothing fabrics, its anti-ultraviolet performance needs to be further improved. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a method for preparing an anti-ultraviolet hygroscopic fiber, comprising the following steps:

[0004] Step (1), firstly coating the surface of gold nanorods with Cu2O to obtain Au@Cu2O, and then growing ZnO on Au@Cu2O to obtain Au@Cu2O / ZnO composite material;

[0005] Step (2), using the Au@Cu2O / ZnO composite material as an additive to react with ethylene glycol, isosorbide and terephthalic acid to obtain modified PET;

[0006] Step (3), the modified PET and the anti-ultraviolet additive are mixed and melt-spun to obtain modified PET fibers; the modified PET fibers are subjected to alkali leaching and deep treatment to obtain activated PET fibers;

[0007] Wherein, the preparation method of the anti-ultraviolet additive comprises the following steps:

[0008] Step S1, using 3-aminoquinoline, 4-aminoquinoline and citric acid as raw materials to prepare carbon dots;

[0009] Step S2, using 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid and cinnamic acid as intercalation agents to prepare intercalation LDH; and then modifying it with 3-aminopropyltriethoxysilane to obtain modified intercalation LDH;

[0010] The carbon dots are grafted onto the modified intercalated LDH to obtain an anti-ultraviolet additive;

[0011] Step (4), reacting 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt with silane coupling agent KH560 to obtain a hydrophilic modifier;

[0012] The hydrophilic modifier, epigallocatechin gallate, was grafted onto activated PET fiber using isophorone diisocyanate as a crosslinking agent to obtain UV-resistant and moisture-absorbing fiber.

[0013] Preferably, in the step (1), the preparation method of the Au@Cu2O / ZnO composite material is as follows: dissolving cupric chloride in ultrapure water, adding sodium dodecyl sulfate and stirring until dissolved, then adding a gold nanorod aqueous dispersion having a concentration of 0.03 g / mL and a sodium hydroxide aqueous solution having a concentration of 0.04 g / mL, stirring at a speed of 100-250 r / min for 10-30 min to obtain a reaction solution; adding hydroxylamine hydrochloride to water under a stirring condition of a speed of 700-900 r / min, then mixing with the above reaction solution, performing a precipitation reaction for 100-150 min, filtering, washing, and drying to obtain Au@Cu2O; wherein the amount ratio of cupric chloride, sodium dodecyl sulfate, gold nanorod aqueous dispersion, sodium hydroxide aqueous solution, and hydroxylamine hydrochloride is (1-2) g:(20-40) g:(6-15) mL:(6-12) mL:(1.4-2.8) g;

[0014] Add Au@Cu2O to a 0.5 mol / L zinc chloride aqueous solution, perform ultrasonic microwave reaction for 100-150 min, filter, wash, and dry to obtain an Au@Cu2O / ZnO composite material; wherein the dosage ratio of Au@Cu2O to the zinc chloride aqueous solution is (0.6-1.2) g: (100-300) mL;

[0015] In the above process, the divalent copper in the copper chloride is reduced to monovalent copper, thereby coating the gold nanorods with Cu2O to obtain Au@Cu2O; then zinc chloride is used as the zinc source to grow and coat ZnO on the Au@Cu2O to obtain an Au@Cu2O / ZnO composite material with a ternary heterostructure.

[0016] Preferably, in the step (2), the preparation method of the modified PET is as follows: under stirring conditions of a rotation speed of 700-900 r / min, the Au@Cu2O / ZnO composite material is added to ethylene glycol, and then isosorbide is added, and microwave reaction is carried out at 160-180°C for 20-40 min, and evaporation concentration is carried out until the water content in the mixed system is 1-2wt%, and terephthalic acid, antimony trioxide, and triethyl phosphate are added, and etherification reaction is carried out at a temperature of 190-210°C and a pressure of 1.8-2.2 MPa for 50-80 min, and then the temperature is raised to 260-280°C, polymerization reaction is carried out for 2-3 h, and cooling to room temperature to obtain the modified PET;

[0017] Furthermore, in the step (2), the mass ratio of the Au@Cu2O / ZnO composite material, ethylene glycol, isosorbide, terephthalic acid, antimony trioxide, and triethyl phosphate is (0.001-0.01):(2-4):(0.7-1.5):(4.2-8.4):(0.05-1):(0.03-0.05);

[0018] In the above process, isosorbide as a modified monomer reacts with ethylene glycol and terephthalic acid to form modified PET, and the metal ions in the Au@Cu2O / ZnO composite material and the oxygen-containing functional groups of the modified PET are combined through strong complexation to form modified PET.

[0019] Preferably, in the step (3), the preparation method of the activated PET fiber comprises: immersing the modified PET fiber in a sodium hydroxide aqueous solution with a concentration of 20 g / L, alkali leaching treatment at 90-100° C. for 20-40 min, transferring the modified PET fiber into a mixed solution of choline chloride and oxalic acid, deep treatment at 40-80° C. for 0.5-2 h, washing, and drying to obtain the activated PET fiber, wherein the mass ratio of choline chloride to oxalic acid in the mixed solution of choline chloride and oxalic acid is 3:2, and the bath ratios of the alkali leaching treatment and the deep treatment are both (25-35):1;

[0020] In the above process, after alkali immersion treatment and deep treatment, more carboxyl and hydroxyl groups are generated on the surface of the modified PET fiber.

[0021] Preferably, in step (3), the method for preparing the anti-ultraviolet additive comprises the following steps:

[0022] Step S1, adding 3-aminoquinoline, 4-aminoquinoline and citric acid into deionized water, ultrasonicating for 10-30 min, reacting at 170-190° C. for 7-9 h, centrifuging to remove precipitate, dialyzing the obtained centrifuge with a 500 Da dialysis bag for 30-40 h, and then drying at 70-90° C. for 70-80 h to obtain carbon dots; the mass ratio of 3-aminoquinoline, 4-aminoquinoline, citric acid and deionized water is (2-7):1:(3-8):(25-75);

[0023] In the above process, anhydrous citric acid was used as raw material and aminoquinoline as nitrogen source, and the hydrothermal carbonization method was used to prepare carbon dots rich in hydroxyl, amino and carboxyl groups;

[0024] Step S2, magnesium nitrate hexahydrate, zinc nitrate hexahydrate, aluminum nitrate nonahydrate, and deionized water are mixed in a mass ratio of (5.1-10.2):(5.9-11.8):(3.8-7.6):(50-100) to form a salt solution; 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, cinnamic acid, sodium hydroxide, and deionized water are mixed in a mass ratio of (3.1-6.2):(1.5-3):(3.8-7.6):(50-100) at 70- Stirring at 80°C to form an alkaline solution; in a nitrogen atmosphere, mixing the salt solution and the alkaline solution at a dripping rate of 1-2 mL / min, stirring and aging the formed precipitate for 20-40 min, filtering, washing, and then dispersing the washed wet filter cake in a solution having a pH value of 6.6-6.7 obtained by mixing cinnamic acid, NaOH, and deionized water, heating and stirring in a water bath at 90-100°C in a nitrogen atmosphere for 11-13 h, centrifuging, washing, and drying to obtain intercalated LDH;

[0025] Add 3-aminopropyltriethoxysilane and intercalated LDH to n-heptane, stir and react at a speed of 600-800 r / min for 20-30 hours, centrifuge, remove the supernatant, wash the centrifuged product with n-heptane for 3-5 times, first vacuum dry at room temperature for 4-6 hours, and then heat at 180-200° C. in vacuum for 3-5 hours to obtain modified intercalated LDH; wherein the mass ratio of 3-aminopropyltriethoxysilane, intercalated LDH, and n-heptane is (6-12):(3-5):(90-200);

[0026] In the above process, magnesium nitrate hexahydrate, zinc nitrate hexahydrate, and aluminum nitrate nonahydrate are used as raw materials to prepare layered double hydroxide (LDH), and during the preparation process, ultraviolet absorbers 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid and cinnamic acid are co-intercalated into the LDH interlayer to obtain intercalated LDH; then, the intercalated LDH is modified with 3-aminopropyltriethoxysilane, and amino groups are introduced into the intercalated LDH to obtain modified intercalated LDH;

[0027] At room temperature, carbon dots are added to methanol, and then modified intercalated LDH is added, and a methanol solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide with a concentration of 0.07 g / L is added dropwise while stirring, and the mixture is stirred for reaction for 20-30 hours. After the reaction is completed, the mixture is filtered, washed, and dried to obtain an anti-ultraviolet additive; wherein the amount ratio of carbon dots, methanol, modified intercalated LDH, and methanol solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is (0.8-1.8) g:(80-150) g:(1.5-3.5) g:(15-30) mL;

[0028] In the above process, the amino groups on the modified intercalated LDH react with the carboxyl groups on the carbon dots to undergo an amidation reaction, thereby grafting the carbon dots onto the modified intercalated LDH.

[0029] Preferably, in step (4), the preparation method of the hydrophilic modifier is as follows: 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt is added to tetrahydrofuran, and then a silane coupling agent KH560 is added in a nitrogen atmosphere, and the mixture is stirred at 75-85° C. for 4-6 hours. After the reaction is completed, the solvent is removed by distillation to obtain a hydrophilic modifier; wherein the mass ratio of 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt, tetrahydrofuran, and silane coupling agent KH560 is (1.9-5.7):(50-80):(2.4-7.2);

[0030] In the above process, the amino group of 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt undergoes a ring-opening reaction with the epoxy group of the silane coupling agent KH560 to generate a hydrophilic modifier containing a hydrophilic sulfonic acid group, an amino group, and a hydroxyl group.

[0031] Preferably, in step (4), the preparation method of the anti-ultraviolet hygroscopic fiber is as follows: adding activated PET fiber to acetone, stirring for 20-40 minutes, then adding isophorone diisocyanate and dibutyltin dilaurate, heating to 53-57°C, stirring for reaction for 3.5-4.5 hours, then adding a hydrophilic modifier, keeping the temperature unchanged and continuing the reaction, detecting the reaction progress by FTIR, when the -NCO peak is at 2260cm -1 When the temperature disappears, the reaction is stopped, and epigallocatechin gallate is added, and the reaction is continued for 1-2 hours. The acetone is evaporated and washed and dried.

[0032] In the above process, the two isocyanate groups of isophorone diisocyanate react with the hydroxyl group on the surface of the activated PET fiber and the hydroxyl group of the hydrophilic modifier respectively, so that the hydrophilic modifier is grafted onto the PET fiber. Furthermore, the phenolic hydroxyl group of epigallocatechin gallate condenses with the siloxy group of the hydrophilic modifier, so that epigallocatechin gallate is also grafted onto the surface of the PET fiber.

[0033] Furthermore, in the step (4), the mass ratio of the activated PET fiber, acetone, isophorone diisocyanate, dibutyltin dilaurate, hydrophilic modifier, and epigallocatechin gallate is (3-8):(100-200):(3.7-7.4):(0.01-0.03):(2.7-5.4):(2.9-5.8).

[0034] The anti-ultraviolet hygroscopic fiber is prepared by adopting the preparation method of the anti-ultraviolet hygroscopic fiber.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] 1. The present invention uses isosorbide as a modified monomer and Au@Cu2O / ZnO composite material as an additive to react with ethylene glycol and terephthalic acid to form a modified PET. Isosorbide and Au@Cu2O / ZnO composite material play an important role in improving the performance of the modified PET. Specifically, the introduction of isosorbide not only increases the hydrophilic hygroscopicity, but also improves the rigidity and UV resistance of the modified PET due to its special bicyclic diol structure; the metal ions in the Au@Cu2O / ZnO composite material and the oxygen-containing functional groups of the modified PET The two nano-Cu2O and ZnO are combined by strong complexation, so that they can be evenly dispersed in the polymer matrix. The heterojunction structure design can significantly improve the antibacterial ability of nano-Cu2O and ZnO. ZnO has good ultraviolet absorption. Coating it on Au@Cu2O can not only improve the anti-ultraviolet performance of the ternary heterogeneous Au@Cu2O / ZnO composite material, but also cut off the contact between Cu2O and air, enhance the stability of Cu2O, and exert a better antibacterial effect. Therefore, the modified PET of the present invention has good hygroscopicity, antibacterial performance, and anti-ultraviolet performance.

[0037] 2. The modified PET and the anti-ultraviolet additive are mixed and melt-spun to obtain the modified PET fiber. During the melt-spinning process, the ternary heterogeneous Au@Cu2O / ZnO composite material migrates on the surface of the modified PET fiber to form uniformly distributed nano-scale grooves. The grooves are interconnected to form wrinkles, which are convenient for the transmission of water and improve the hygroscopic performance of the modified PET fiber. Further, the modified PET fiber is subjected to alkali immersion treatment and deep treatment to produce more hydrophilic carboxyl and hydroxyl groups on the surface of the modified PET fiber. Then, a hydrophilic modifier containing hydrophilic sulfonic acid, amino and hydroxyl groups is connected to the surface of the modified PET fiber in the form of a chemical bond. The increase of a large number of hydrophilic groups improves the hydrophilicity and hygroscopicity of the fiber. Then, epigallocatechin gallate is also connected to the surface of the PET fiber through a condensation reaction with the hydrophilic modifier, and hydrophilic and antibacterial phenolic hydroxyl groups and an aromatic hydrocarbon ring structure with ultraviolet blocking properties are introduced, thereby further improving the hygroscopic performance, antibacterial performance and anti-ultraviolet performance of the PET fiber.

[0038] 3. The present invention co-intercalates the ultraviolet absorber 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid and cinnamic acid into the interlayer of LDH (layered double hydroxide) to obtain intercalated LDH. LDH has an ultraviolet scattering effect due to its lamellar structure. 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid and cinnamic acid are co-intercalated, and the π-π conjugated interaction between the two can broaden the ultraviolet absorption band. The synergistic effect of the two has stronger ultraviolet absorption ability and a wider ultraviolet absorption band. The physical blocking of LDH is combined with the chemical absorption of the ultraviolet absorber, so that the intercalated LDH has good The invention discloses a method for grafting carbon dots on the intercalated LDH. The carbon dots of the invention use 3-aminoquinoline and 4-aminoquinoline as nitrogen sources, and the amino group is located on the benzene ring, which is a heterocyclic compound. Compared with the benzene ring raw materials, the absorption band of the obtained carbon dots is enhanced and moved, and the carbon dots have the absorption characteristics of the entire ultraviolet band, and can cooperate with the intercalated LDH to exert a better anti-ultraviolet effect. In addition, since the carbon dots contain abundant hydroxyl groups, amino groups and carboxyl groups, the hydrophilicity of the ultraviolet absorber can be increased, and a large number of hydrogen bonds can be formed with the modified PET, thereby improving the interface compatibility between the ultraviolet absorber and the modified PET. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is a process flow chart of the preparation method of the anti-ultraviolet hygroscopic fiber of the present invention;

[0040] Figure 2 It is a comparison chart of moisture regain test of the anti-ultraviolet moisture absorption fiber of Examples 2-4 of the present invention and Comparative Examples 3-10;

[0041] Figure 3 It is a comparison chart of the antibacterial rate test of the anti-ultraviolet moisture absorption fiber of Examples 2-4 of the present invention and Comparative Examples 3-10;

[0042] Figure 4 It is a comparison chart of the elongation at break retention rate test of the anti-ultraviolet hygroscopic fibers of Examples 2-4 of the present invention and Comparative Examples 3-10. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0044] Example 1

[0045] This embodiment discloses a method for preparing an anti-ultraviolet additive, comprising the following steps:

[0046] Step S1, adding 3-aminoquinoline, 4-aminoquinoline and citric acid into deionized water, ultrasonicating for 20 minutes, reacting at 180°C for 8 hours, centrifuging to remove the precipitate, dialyzing the obtained centrifuge with a 500Da dialysis bag for 35 hours, and then drying at 80°C for 75 hours to obtain carbon dots; the mass ratio of 3-aminoquinoline, 4-aminoquinoline, citric acid and deionized water is 4.5:1:5.5:50;

[0047] Step S2, dissolving 7.6g of magnesium nitrate hexahydrate, 8.9g of zinc nitrate hexahydrate and 5.7g of aluminum nitrate nonahydrate in 75g of deionized water to form a salt solution; dissolving 4.7g of 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, 2.3g of cinnamic acid and 5.7g of sodium hydroxide in 75g of deionized water, and stirring at 75°C to form an alkaline solution; in a nitrogen atmosphere, the salt solution and the alkaline solution are mixed at a drip rate of 1.5mL / min, and the formed precipitate is stirred and aged for 30min, filtered, and the filter cake is washed with deionized water 6 times, and then the washed wet filter cake is dispersed in 225g of a solution with a pH value of 6.6 obtained by mixing cinnamic acid, NaOH and deionized water, and heated in a water bath at 95°C in a nitrogen atmosphere for 12h, centrifuged, and the obtained precipitate is washed with deionized water 4 times, ethanol 2 times, acetone 2 times, and dried to obtain intercalated LDH;

[0048] 9 g of 3-aminopropyltriethoxysilane and 4 g of intercalated LDH were added to 150 g of n-heptane, stirred at 700 r / min for 25 h, centrifuged, and the supernatant was removed. The centrifuged product was washed with n-heptane for 4 times, first vacuum dried at room temperature for 5 h, and then heated at 190° C. in vacuum for 4 h to obtain modified intercalated LDH;

[0049] At room temperature, 1.3 g of carbon dots were added to 115 g of methanol, and then 2.5 g of modified intercalated LDH was added. While stirring, 22.5 mL of a methanol solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide with a concentration of 0.07 g / L was added dropwise. The reaction was stirred for 25 hours. After the reaction was completed, the mixture was filtered, washed, and dried to obtain an anti-ultraviolet additive.

[0050] Example 2

[0051] This embodiment discloses a method for preparing an anti-ultraviolet hygroscopic fiber, comprising the following steps:

[0052] Step (1), dissolving 1g of copper chloride in 200g of ultrapure water, adding 20g of sodium dodecyl sulfate and stirring until dissolved, then adding 6mL of 0.03g / mL gold nanorod aqueous dispersion and 6mL of 0.04g / mL sodium hydroxide aqueous solution, stirring at a speed of 100r / min for 30min to obtain a reaction solution; under a stirring condition of a speed of 700r / min, adding 1.4g of hydroxylamine hydrochloride to 10g of water, and then mixing with the above reaction solution, precipitation reaction for 100min, filtering, washing, and drying to obtain Au@Cu2O;

[0053] 0.6 g Au@Cu2O was added into 100 mL of 0.5 mol / L zinc chloride aqueous solution, reacted in an ultrasonic microwave co-reactor for 100 min, filtered, washed, and dried to obtain Au@Cu2O / ZnO composite material;

[0054] Step (2), adding the Au@Cu2O / ZnO composite material to ethylene glycol under stirring at a speed of 700 r / min, then adding isosorbide, reacting at 160° C. for 40 min by microwave, evaporating and concentrating until the water content in the mixed system is 1wt%, adding terephthalic acid, antimony trioxide and triethyl phosphate, and carrying out etherification reaction at a temperature of 190° C. and a pressure of 1.8 MPa for 80 min, then heating to 260° C., polymerizing for 3 h, and cooling to room temperature to obtain modified PET; wherein the mass ratio of the Au@Cu2O / ZnO composite material, ethylene glycol, isosorbide, terephthalic acid, antimony trioxide and triethyl phosphate is 0.001:2:0.7:4.2:0.05:0.03;

[0055] Step (3), the modified PET and the anti-ultraviolet additive are mixed and melt-spun to obtain modified PET fibers; the modified PET fibers are immersed in a sodium hydroxide aqueous solution with a concentration of 20 g / L, and after alkali immersion treatment at 90° C. for 40 min, the modified PET fibers are transferred into a mixed solution of choline chloride and oxalic acid, and deep-treated at 40° C. for 2 h, washed, and dried to obtain activated PET fibers, wherein the mass ratio of choline chloride to oxalic acid in the mixed solution of choline chloride and oxalic acid is 3:2, and the bath ratios of the alkali immersion treatment and the deep treatment are both 25:1;

[0056] Step (4), adding 1.9 g of 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt to 50 g of tetrahydrofuran, and then adding 2.4 g of silane coupling agent KH560 in a nitrogen atmosphere, stirring and reacting at 75° C. for 6 h. After the reaction is completed, distilling off the solvent to obtain a hydrophilic modifier;

[0057] 3 g of activated PET fiber was added to 100 g of acetone and stirred for 20 min. Then 3.7 g of isophorone diisocyanate and 0.01 g of dibutyltin dilaurate were added. The mixture was heated to 53 °C and stirred for 4.5 h. Then 2.7 g of hydrophilic modifier was added. The temperature was kept constant and the reaction was continued. The reaction progress was monitored by FTIR. When the -NCO peak was at 2260 cm -1 The reaction was stopped when the carbonyl group disappeared, and 2.9 g of epigallocatechin gallate was added, and the reaction was continued for 1 h. The acetone was evaporated to remove the acetone, and the fiber was washed and dried to obtain the UV-resistant moisture-absorbing fiber.

[0058] Example 3

[0059] This embodiment discloses a method for preparing an anti-ultraviolet hygroscopic fiber, comprising the following steps:

[0060] Step (1), dissolving 2g of copper chloride in 300g of ultrapure water, adding 40g of sodium dodecyl sulfate and stirring until dissolved, then adding 15mL of a gold nanorod aqueous dispersion with a concentration of 0.03g / mL and 12mL of a sodium hydroxide aqueous solution with a concentration of 0.04g / mL, stirring at a speed of 250r / min for 10min to obtain a reaction solution; under a stirring condition of a speed of 900r / min, adding 2.8g of hydroxylamine hydrochloride to 20g of water, and then mixing with the above reaction solution, precipitation reaction for 150min, filtering, washing, and drying to obtain Au@Cu2O;

[0061] 1.2 g Au@Cu2O was added into 300 mL of 0.5 mol / L zinc chloride aqueous solution, reacted in an ultrasonic microwave co-reactor for 150 min, filtered, washed, and dried to obtain Au@Cu2O / ZnO composite material;

[0062] Step (2), adding the Au@Cu2O / ZnO composite material to ethylene glycol under stirring at a speed of 900 r / min, then adding isosorbide, reacting at 180° C. for 20 min by microwave, evaporating and concentrating until the water content in the mixed system is 2wt%, adding terephthalic acid, antimony trioxide and triethyl phosphate, and carrying out etherification reaction at a temperature of 210° C. and a pressure of 2.2 MPa for 50 min, then heating to 280° C., polymerizing for 2 h, and cooling to room temperature to obtain modified PET; wherein the mass ratio of the Au@Cu2O / ZnO composite material, ethylene glycol, isosorbide, terephthalic acid, antimony trioxide and triethyl phosphate is 0.01:4:1.5:8.4:1:0.05;

[0063] Step (3), the modified PET and the anti-ultraviolet additive are mixed and melt-spun to obtain modified PET fibers; the modified PET fibers are immersed in a sodium hydroxide aqueous solution with a concentration of 20 g / L, and after alkali immersion treatment at 100° C. for 20 min, they are transferred into a mixed solution of choline chloride and oxalic acid, and deep-treated at 80° C. for 0.5 h, washed, and dried to obtain activated PET fibers, wherein the mass ratio of choline chloride to oxalic acid in the mixed solution of choline chloride and oxalic acid is 3:2, and the bath ratios of the alkali immersion treatment and the deep treatment are both 35:1;

[0064] Step (4), adding 5.7 g of 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt to 80 g of tetrahydrofuran, and then adding 7.2 g of silane coupling agent KH560 in a nitrogen atmosphere, stirring and reacting at 85° C. for 6 h. After the reaction is completed, distilling off the solvent to obtain a hydrophilic modifier;

[0065] 8 g of activated PET fiber was added to 200 g of acetone and stirred for 40 min. Then 7.4 g of isophorone diisocyanate and 0.03 g of dibutyltin dilaurate were added. The mixture was heated to 57 °C and stirred for 4.5 h. Then 5.4 g of hydrophilic modifier was added. The temperature was kept constant and the reaction was continued. The reaction progress was monitored by FTIR. When the -NCO peak was at 2260 cm -1 The reaction was stopped when the carbonyl group disappeared, and 5.8 g of epigallocatechin gallate was added, and the reaction was continued for 2 h. The acetone was evaporated to remove the acetone, and the fiber was washed and dried to obtain the UV-resistant moisture-absorbing fiber.

[0066] Example 4

[0067] This embodiment discloses a method for preparing an anti-ultraviolet hygroscopic fiber, comprising the following steps:

[0068] Step (1), dissolving 1.5 g of copper chloride in 250 g of ultrapure water, adding 30 g of sodium dodecyl sulfate and stirring until dissolved, then adding 10.5 mL of a gold nanorod aqueous dispersion having a concentration of 0.03 g / mL and 9 mL of a sodium hydroxide aqueous solution having a concentration of 0.04 g / mL, stirring at a speed of 150 r / min for 20 min to obtain a reaction solution; under a stirring condition of a speed of 800 r / min, adding 2.1 g of hydroxylamine hydrochloride to 15 g of water, then mixing with the above reaction solution, precipitating and reacting for 120 min, filtering, washing, and drying to obtain Au@Cu2O;

[0069] 0.9 g Au@Cu2O was added into 200 mL of 0.5 mol / L zinc chloride aqueous solution, reacted in an ultrasonic microwave co-reactor for 120 min, filtered, washed, and dried to obtain Au@Cu2O / ZnO composite material;

[0070] Step (2), adding the Au@Cu2O / ZnO composite material to ethylene glycol under stirring at a speed of 800 r / min, then adding isosorbide, reacting at 170° C. for 30 min by microwave, evaporating and concentrating until the water content in the mixed system is 1.5wt%, adding terephthalic acid, antimony trioxide and triethyl phosphate, and carrying out etherification reaction at a temperature of 200° C. and a pressure of 2 MPa for 70 min, then heating to 270° C., polymerizing for 2.5 h, and cooling to room temperature to obtain modified PET; wherein the mass ratio of the Au@Cu2O / ZnO composite material, ethylene glycol, isosorbide, terephthalic acid, antimony trioxide and triethyl phosphate is 0.005:3:1.1:6.3:0.08:0.04;

[0071] Step (3), the modified PET and the anti-ultraviolet additive are mixed and melt-spun to obtain modified PET fibers; the modified PET fibers are immersed in a sodium hydroxide aqueous solution with a concentration of 20 g / L, and after alkali immersion treatment at 95° C. for 30 min, the modified PET fibers are transferred into a mixed solution of choline chloride and oxalic acid, and deep-treated at 60° C. for 1.5 h, washed, and dried to obtain activated PET fibers, wherein the mass ratio of choline chloride to oxalic acid in the mixed solution of choline chloride and oxalic acid is 3:2, and the bath ratios of the alkali immersion treatment and the deep treatment are both 30:1;

[0072] Step (4), adding 3.8 g of 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt to 65 g of tetrahydrofuran, and then adding 4.8 g of silane coupling agent KH560 in a nitrogen atmosphere, stirring and reacting at 80° C. for 5 h. After the reaction is completed, distilling off the solvent to obtain a hydrophilic modifier;

[0073] 5.5 g of activated PET fiber was added to 150 g of acetone and stirred for 30 min. Then, 5.6 g of isophorone diisocyanate and 0.02 g of dibutyltin dilaurate were added. The mixture was heated to 55 °C and stirred for 4 h. Then, 4 g of hydrophilic modifier was added and the temperature was kept constant to continue the reaction. The reaction progress was monitored by FTIR. When the -NCO peak was at 2260 cm -1 The reaction was stopped when the carbonyl group disappeared, and 4.3 g of epigallocatechin gallate was added, and the reaction was continued for 1.5 h. The acetone was evaporated to remove the acetone, and the fiber was washed and dried to obtain the UV-resistant moisture-absorbing fiber.

[0074] The anti-ultraviolet additives in the above Examples 2-4 are the anti-ultraviolet additives prepared in Example 1.

[0075] Comparative Example 1

[0076] Comparative Example 1 Compared with Example 1, in the process of preparing intercalated LDH in Comparative Example 1, cinnamic acid was not added, and other conditions remained unchanged.

[0077] Comparative Example 2

[0078] Comparative Example 2 Compared with Example 1, in the process of preparing intercalated LDH in Comparative Example 2, no 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid was added, and other conditions remained unchanged.

[0079] Comparative Example 3

[0080] Comparative Example 3 Compared with Example 4, Comparative Example 3 uses the anti-ultraviolet additive prepared in Comparative Example 1, and other conditions remain unchanged.

[0081] Comparative Example 4

[0082] Comparative Example 4 Compared with Example 4, Comparative Example 4 adopts the anti-ultraviolet additive prepared in Comparative Example 1, and other conditions remain unchanged.

[0083] Comparative Example 5

[0084] Comparative Example 5 Compared with Example 4, in the process of preparing the modified PET fiber, the modified intercalated LDH was used to replace the anti-ultraviolet additive, and other conditions remained unchanged.

[0085] Comparative Example 6

[0086] Comparative Example 6 Compared with Example 4, in the process of preparing the modified PET in Comparative Example 6, Au@Cu2O is used instead of the Au@Cu2O / ZnO composite material, and other conditions remain unchanged.

[0087] Comparative Example 7

[0088] Comparative Example 7 Compared with Example 4, in the process of preparing the modified PET in Comparative Example 7, no Au@Cu2O / ZnO composite material was added, and other conditions remained unchanged.

[0089] Comparative Example 8

[0090] Comparative Example 8 Compared with Example 4, in the process of preparing the modified PET in Comparative Example 8, no isosorbide was added, and other conditions remained unchanged.

[0091] Comparative Example 9

[0092] Comparative Example 9 Compared with Example 4, in the process of preparing the anti-ultraviolet hygroscopic fiber in Comparative Example 9, no hydrophilic modifier was added, and other conditions remained unchanged.

[0093] Comparative Example 10

[0094] Comparative Example 10 Compared with Example 4, in the process of preparing the anti-ultraviolet hygroscopic fiber in Comparative Example 10, epigallocatechin gallate was not added, and other conditions remained unchanged.

[0095] In the above embodiments and comparative examples, the gold nanorods are water-soluble gold nanorods with absorption peak of 808 nm±10 nm, diameter of 10 nm, and length of 43 nm, and are from Beijing Zhongke Keyou Technology Co., Ltd.

[0096] Experimental example

[0097] The performance of the anti-ultraviolet hygroscopic fibers prepared in Examples 2-4 and Comparative Examples 3-10 was tested.

[0098] 1. Moisture regain test: According to GB / T6503-2017 "Test method for moisture regain of chemical fibers". Test method: After placing the fiber sample in a constant temperature and humidity environment (25°C, 60% RH) for 48 hours, weigh a certain mass of fiber and place it in an oven and weigh it (g). After drying for 1 hour, weigh the mass every 10 minutes until the mass remains constant and is recorded as G0 (g). The formula for calculating the moisture regain W is as follows:

[0099]

[0100] Note: The official moisture regain of polyester fiber is 0.4%.

[0101] 2. Anti-ultraviolet performance test: The XL-1A filament tensile tester was used to test the elongation at break of the fiber samples. Then, each group of samples was subjected to artificial accelerated aging in a UV accelerated aging tester for 360 hours. The elongation at break of each group of samples after UV aging was tested, and the retention rate of the elongation at break was calculated to characterize the anti-ultraviolet performance of the samples.

[0102] Elongation at break test method: pass the sample around the yarn guide hook and the yarn guide wheel, and pass it downward through the upper and lower clamps to ensure that the sample is straight without relaxation. Apply a pre-tension of 10cN to the sample, and then the lower clamp drives the sample down until the sample breaks and then returns to its original position to obtain the elongation at break of the sample. The clamping distance is 250mm, the stretching speed is 250mm / min, and each sample is repeated more than 10 times, and the test results are averaged.

[0103] 3. Antibacterial performance test: According to the method of AATCC 100-1999; the inoculated bacteria are Escherichia coli; the polyester fiber is placed in a PBS buffer solution containing Escherichia coli (2.0×10 8 CFU / mL), shake and contact for 30 minutes, immerse it in a sterile sodium thiosulfate solution, centrifuge it, dilute the solution continuously with PBS buffer solution, and then place it in agar medium, culture it at 37℃ for 24 hours, count the number of surviving bacteria, and calculate the inhibition rate. The calculation formula of the inhibition rate is as follows:

[0104] Antibacterial rate = (AB) / A×100%,

[0105] Among them, A is the bacterial count (CFU / mL) before culture after serial dilution; A is the bacterial count (CFU / mL) after culture. The test results are shown in Table 1:

[0106] Table 1

[0107] Moisture regain / % Antibacterial rate / % Retention rate of elongation at break / % Example 2 3.87 99.36 94.7 Example 3 3.99 99.58 95.8 Example 4 3.92 99.44 95.3 Comparative Example 3 3.90 99.34 93.3 Comparative Example 4 3.91 99.44 93.0 Comparative Example 5 3.80 99.43 91.4 Comparative Example 6 3.92 98.71 92.7 Comparative Example 7 3.58 97.39 92.6 Comparative Example 8 3.83 99.43 94.3 Comparative Example 9 3.53 99.44 95.2 Comparative Example 10 3.72 97.45 93.7

[0108] It can be seen from the test results in Table 1 that the anti-ultraviolet hygroscopic fibers prepared in Examples 2-4 of the present invention have excellent anti-ultraviolet performance, hygroscopic performance and antibacterial performance. From the comparison between comparative examples 3-4 and example 4, it can be seen that the ultraviolet absorbers 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid and cinnamic acid have a chemical absorption effect on ultraviolet rays, improve the anti-ultraviolet performance of the fiber, and cinnamic acid can inhibit the growth of bacteria, so it has a certain effect on the antibacterial performance of the fiber; from the comparison between comparative example 5 and example 4, it can be seen that the carbon dots of the present invention can play a better anti-ultraviolet effect in synergy with the intercalated LDH due to their own ultraviolet absorption performance, and the carbon dots contain rich hydroxyl, amino and carboxyl groups, which can increase the hydrophilicity of the ultraviolet absorber, and form a large number of hydrogen bonds with the modified PET, thereby improving the interfacial compatibility between the ultraviolet absorber and the modified PET, thereby improving the hygroscopicity and anti-ultraviolet performance of the fiber; from the comparison between comparative examples 6-7 and example 4, it can be seen that the heterojunction structure design of the Au@Cu2O / ZnO composite material can significantly improve the antibacterial ability of nano-Cu2O and ZnO, and ZnO has good ultraviolet absorption. O, can improve the anti-ultraviolet performance of the ternary heterogeneous Au@Cu2O / ZnO composite material, and can also enhance the stability of Cu2O by cutting off the contact between Cu2O and air, and exert a better antibacterial effect; and the ternary heterogeneous Au@Cu2O / ZnO composite material forms wrinkles by migrating on the surface of the modified PET fiber to form uniformly distributed nano-scale grooves, thereby improving the hygroscopicity of the modified PET fiber; from the comparison of comparative example 8 with embodiment 4, it can be seen that the introduction of isosorbide will not only increase the hydrophilic hygroscopicity, but also improve the anti-ultraviolet performance of the modified PET due to its special bicyclic diol structure; from the comparison of comparative example 9 with embodiment 4, it can be seen that the presence of hydrophilic sulfonic acid, amino and hydroxyl groups in the hydrophilic modifier improves the hydrophilic hygroscopicity of the fiber; from the comparison of comparative example 10 with embodiment 4, it can be seen that epigallocatechin gallate introduces hydrophilic and antibacterial phenolic hydroxyl groups and aromatic hydrocarbon ring structures with ultraviolet blocking properties on the fiber surface to improve the comprehensive performance of the fiber.

[0109] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an anti-ultraviolet hygroscopic fiber, characterized in that: The following steps are involved: Step (1), firstly coating the surface of gold nanorods with Cu2O to obtain Au@Cu2O, and then growing ZnO on Au@Cu2O to obtain Au@Cu2O / ZnO composite material; Step (2), using the Au@Cu2O / ZnO composite material as an additive to react with ethylene glycol, isosorbide and terephthalic acid to obtain modified PET; Step (3), the modified PET and the anti-ultraviolet additive are mixed and melt-spun to obtain modified PET fibers; The modified PET fiber is subjected to alkali leaching treatment and deep treatment to obtain activated PET fiber; The deep treatment comprises transferring the modified PET fiber after alkali leaching into a mixture of choline chloride and oxalic acid, deep treating at 40-80° C. for 0.5-2 h, washing, and drying; The mass ratio of choline chloride to oxalic acid in the mixed solution of choline chloride and oxalic acid is 3:2, and the bath ratio of deep treatment is (25-35):1; The preparation method of the anti-ultraviolet additive comprises the following steps: Step S1, using 3-aminoquinoline, 4-aminoquinoline and citric acid as raw materials to prepare carbon dots; Step S2, using 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid and cinnamic acid as intercalation agents to prepare intercalation LDH; and then modifying it with 3-aminopropyltriethoxysilane to obtain modified intercalation LDH; The carbon dots are grafted onto the modified intercalated LDH to obtain an anti-ultraviolet additive; Step (4), reacting 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt with silane coupling agent KH560 to obtain a hydrophilic modifier; The hydrophilic modifier, epigallocatechin gallate, was grafted onto activated PET fiber using isophorone diisocyanate as a crosslinking agent to obtain UV-resistant and moisture-absorbing fiber.

2. The method for preparing the anti-ultraviolet hygroscopic fiber according to claim 1, characterized in that: In the step (1), the preparation method of the Au@Cu2O / ZnO composite material is as follows: dissolving cupric chloride in ultrapure water, adding sodium dodecyl sulfate and stirring until dissolved, then adding a gold nanorod aqueous dispersion with a concentration of 0.03 g / mL and a sodium hydroxide aqueous solution with a concentration of 0.04 g / mL, stirring at a speed of 100-250 r / min for 10-30 min to obtain a reaction solution; adding hydroxylamine hydrochloride to water under stirring conditions of a speed of 700-900 r / min, then mixing with the above reaction solution, performing precipitation reaction for 100-150 min, filtering, washing, and drying to obtain Au@Cu2O; wherein the amount ratio of cupric chloride, sodium dodecyl sulfate, gold nanorod aqueous dispersion, sodium hydroxide aqueous solution, and hydroxylamine hydrochloride is (1-2) g:(20-40) g:(6-15) mL:(6-12) mL:(1.4-2.8) g; Au@Cu2O is added to a 0.5 mol / L zinc chloride aqueous solution, subjected to ultrasonic microwave reaction for 100-150 min, filtered, washed, and dried to obtain an Au@Cu2O / ZnO composite material; wherein the dosage ratio of Au@Cu2O to the zinc chloride aqueous solution is (0.6-1.2) g:(100-300) mL.

3. The method for preparing the anti-ultraviolet hygroscopic fiber according to claim 1, characterized in that: In the step (2), the preparation method of the modified PET is as follows: under stirring conditions of a rotation speed of 700-900 r / min, the Au@Cu2O / ZnO composite material is added to ethylene glycol, and then isosorbide is added, and microwave reaction is carried out at 160-180°C for 20-40 min, and evaporation concentration is carried out until the water content in the mixed system is 1-2wt%, terephthalic acid, antimony trioxide, and triethyl phosphate are added, and etherification reaction is carried out at a temperature of 190-210°C and a pressure of 1.8-2.2 MPa for 50-80 min, and then the temperature is raised to 260-280°C, polymerization reaction is carried out for 2-3 h, and cooling is carried out to room temperature to obtain the modified PET.

4. The method for preparing the anti-ultraviolet hygroscopic fiber according to claim 3, characterized in that: In the step (2), the mass ratio of the Au@Cu2O / ZnO composite material, ethylene glycol, isosorbide, terephthalic acid, antimony trioxide, and triethyl phosphate is (0.001-0.01):(2-4):(0.7-1.5):(4.2-8.4):(0.05-1):(0.03-0.05).

5. The method for preparing the anti-ultraviolet hygroscopic fiber according to claim 1, characterized in that: In the step (3), the alkali immersion treatment comprises immersing the modified PET fiber in a sodium hydroxide aqueous solution with a concentration of 20 g / L, and alkali immersion treatment at 90-100° C. for 20-40 min, and the bath ratio of the alkali immersion treatment is (25-35):

1.

6. The method for preparing the anti-ultraviolet hygroscopic fiber according to claim 1, characterized in that: In step (3), the method for preparing the anti-ultraviolet additive comprises the following steps: Step S1, adding 3-aminoquinoline, 4-aminoquinoline and citric acid into deionized water, ultrasonicating for 10-30 min, reacting at 170-190° C. for 7-9 h, centrifuging to remove precipitate, dialyzing the obtained centrifuge with a 500 Da dialysis bag for 30-40 h, and then drying at 70-90° C. for 70-80 h to obtain carbon dots; the mass ratio of 3-aminoquinoline, 4-aminoquinoline, citric acid and deionized water is (2-7):1:(3-8):(25-75); Step S2, magnesium nitrate hexahydrate, zinc nitrate hexahydrate, aluminum nitrate nonahydrate, and deionized water are mixed in a mass ratio of (5.1-10.2):(5.9-11.8):(3.8-7.6):(50-100) to form a salt solution; 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, cinnamic acid, sodium hydroxide, and deionized water are mixed in a mass ratio of (3.1-6.2):(1.5-3):(3.8-7.6):(50-100) at 70- Stirring at 80°C to form an alkaline solution; in a nitrogen atmosphere, mixing the salt solution and the alkaline solution at a dripping rate of 1-2 mL / min, stirring and aging the formed precipitate for 20-40 min, filtering, washing, and then dispersing the washed wet filter cake in a solution having a pH value of 6.6-6.7 obtained by mixing cinnamic acid, NaOH, and deionized water, heating and stirring in a water bath at 90-100°C in a nitrogen atmosphere for 11-13 h, centrifuging, washing, and drying to obtain intercalated LDH; Add 3-aminopropyltriethoxysilane and intercalated LDH to n-heptane, stir and react at a speed of 600-800 r / min for 20-30 hours, centrifuge, remove the supernatant, wash the centrifuged product with n-heptane for 3-5 times, first vacuum dry at room temperature for 4-6 hours, and then heat at 180-200° C. in vacuum for 3-5 hours to obtain modified intercalated LDH; wherein the mass ratio of 3-aminopropyltriethoxysilane, intercalated LDH, and n-heptane is (6-12):(3-5):(90-200); At room temperature, carbon dots are added to methanol, and then modified intercalated LDH is added, and a methanol solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide with a concentration of 0.07 g / L is added dropwise while stirring, and the reaction is stirred for 20-30 hours. After the reaction is completed, the mixture is filtered, washed, and dried to obtain an anti-ultraviolet additive; wherein the amount ratio of carbon dots, methanol, modified intercalated LDH, and methanol solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is (0.8-1.8) g:(80-150) g:(1.5-3.5) g:(15-30) mL.

7. The method for preparing the anti-ultraviolet hygroscopic fiber according to claim 1, characterized in that: In the step (4), the preparation method of the hydrophilic modifier is as follows: 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt is added to tetrahydrofuran, and then a silane coupling agent KH560 is added in a nitrogen atmosphere, and the reaction is stirred at 75-85° C. for 4-6 hours. After the reaction is completed, the solvent is distilled off to obtain a hydrophilic modifier; wherein the mass ratio of 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt, tetrahydrofuran, and silane coupling agent KH560 is (1.9-5.7):(50-80):(2.4-7.2).

8. The method for preparing the anti-ultraviolet hygroscopic fiber according to claim 1, characterized in that: In the step (4), the preparation method of the anti-ultraviolet hygroscopic fiber is as follows: adding activated PET fiber to acetone, stirring for 20-40 minutes, then adding isophorone diisocyanate and dibutyltin dilaurate, heating to 53-57°C, stirring for reaction for 3.5-4.5 hours, then adding a hydrophilic modifier, keeping the temperature unchanged and continuing the reaction, and detecting the reaction progress by FTIR. When the -NCO peak is at 2260cm -1 The reaction was stopped when the color disappeared, and epigallocatechin gallate was added, and the reaction was continued for 1-2 hours. The acetone was evaporated to remove the acetone, and the mixture was washed and dried.

9. The method for preparing the anti-ultraviolet hygroscopic fiber according to claim 8, characterized in that: In the step (4), the mass ratio of the activated PET fiber, acetone, isophorone diisocyanate, dibutyltin dilaurate, hydrophilic modifier, and epigallocatechin gallate is (3-8):(100-200):(3.7-7.4):(0.01-0.03):(2.7-5.4):(2.9-5.8).

10. An anti-ultraviolet hygroscopic fiber prepared by the method for preparing the anti-ultraviolet hygroscopic fiber according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A preparation process of moisture-absorbing antibacterial fiber fabric

    CN117845364B

  • Supramolecular intercalated structure light stabilizer and preparation method thereof

    CN107629310A

  • Antibacterial and antiviral non-woven fabric and preparation method thereof

    CN112482015A